Clinical and biochemical characterization of hereditary transthyretin amyloidosis caused by E61K mutation - Chu, Xujun; Wang, Mengdie; Tang, Ran; Huang, Yanan; Yu, Jiaxi; Cao, Yunfeng; Zheng, Yilei; Xie, Zhiying; Deng, Jianwen; Wang, Zhi; Ma, Wei; Song, Wenjing; et al. (Frontiers in Molecular Neuroscience, 2022)
Objects: This study was intended to find out more about the clinical characterizations of patients carrying transthyretin (TTR) E61K (p.Glu81Lys) gene mutation and the biochemical characterization of this mutant protein. Materials and methods: Five patients who had been diagnosed with hereditary transthyretin amyloidosis and two asymptomatic carriers carrying TTR E61K gene mutation were reported. Biochemical and biophysical tests were conducted to observe the thermodynamic and kinetic stability. Fibril formation tests measured by turbidity assay were performed to explore the pathogenicity of this mutation. Kinetic stabilizer responsiveness was measured to determine the inhibitory effect on protein aggregation. Results: The average age of onset for the five patients was 62 years, and the course of the disease ranged from 2 to 10 years. Cardiac disease was prominent in this group of patients. Nerve pathology revealed a mildly to moderately reduced myelinated fiber density and muscle pathology showed predominant neurogenic impairment accompanied by possible myogenic impairment. E61K-TTR was characterized as a kinetically destabilized protein compared to WT-TTR but its thermodynamic stability was not compromised. In addition, the subunit exchange of E61K with WT-TTR further destabilized the heterozygous tetramer. Meanwhile, the E61K:WT heterozygous tetramer exhibited a poor response to kinetic stabilizers in the fibril formation assay. Finally, the serum TTR tetramer concentration was low in E61K-TTR symptomatic patients and in one asymptomatic gene carrier. Vyndamax (Tafamidis) could increase the TTR tetramer concentration. Conclusions: Patients with E61K mutation tended to be late-onset. The concentration of TTR tetramer in the serum might serve as a biomarker to monitor disease progress, therapeutic window time, and therapeutic response to TTR kinetic stabilizer drugs.